1988
DOI: 10.1016/0014-5793(88)80807-x
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of cDNA clones for maize phosphoenolpyruvate carboxylase involved in C4 photosynthesis Nucleotide sequence of entire open reading frame and evidence for polyadenylation of mRNA at multiple sites in vivo

Abstract: Four clones of cDNA for phosphoenolpyruvate carboxylase [EC 4.1.1.31] were obtained from a maize green leaf eDNA library by colony hybridization. The largest eDNA was of full-length (3335 nucleotides), being 243 nucleotides longer than the cDNA cloned previously ) Nucleic Acids Res. 14, 1615-1628. Alignment of the sequence for the N-terminal coding region found in two of the four clones with the sequence reported previously, established the sequence of the entire coding region for the enzyme. The sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…pTM94 and pEM94 (27), which contain the entire coding region of the cDNA of ZmPEPC, were used as starting materials. During the course of this study, many errors were found in the sequence that had been reported by us previously (28,29). Thus we re-determined and revised the sequence (Fig.…”
Section: Methodsmentioning
confidence: 79%
“…pTM94 and pEM94 (27), which contain the entire coding region of the cDNA of ZmPEPC, were used as starting materials. During the course of this study, many errors were found in the sequence that had been reported by us previously (28,29). Thus we re-determined and revised the sequence (Fig.…”
Section: Methodsmentioning
confidence: 79%
“…Consensus intron/exon splice sites (aGGTaag-tgcAGg) are conserved. Generally, a classical gene organization is observed, although in some C 4 -and C 3 -type Ppc genes there is no typical TATA box, and multiple polyadenylation sites are found in the 3′-untranslated region (15,43,74,132).…”
Section: Ppc and Pepc Sequence Comparisonsmentioning
confidence: 99%
“…In vitro phosphorylation of PEPC by an endogenous protein kinase and accompanying changes in the kinetic properties were also reported [4]. Although the complete primary structure of maize PEPC involved in the C4 photosynthesis was deduced from the nucleotide sequence of the cDNA by us [5,6], the site of the seryl residue which undergoes phosphorylation has not yet been elucidated. In this study, we found that the maize PEPC was a good substrate for mammalian A-kinase in vitro and that the phosphorylation caused the changes in kinetic properties, which were very similar to the phosphorylation observed in vivo [3].…”
Section: Introductionmentioning
confidence: 98%